2009
DOI: 10.1021/om900223p
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Cinnamaldehyde and Other α,β-Unsaturated Substrates Catalyzed by Rhodium and Ruthenium Complexes

Abstract: The complexes [Rh(PhBP 3 )(cod)] ( 1) and [{Ru(PhBP 3 )(µ-Cl)} 2 ] (8), containing the tripodal phosphanoborate ligand [PhB(CH 2 PPh 2 ) 3 ] -, are efficient catalysts for the selective hydrogenation of cinnamaldehyde to the corresponding allyl alcohol. Complex 8 is one of the most efficient catalysts reported to date for this reaction, in terms of activity (TOF 527 h -1 ) and selectivity (g97%) under mild reaction conditions (6.8 atm H 2 , 75 °C). The rhodium system also displays good catalytic features in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 65 publications
0
28
0
2
Order By: Relevance
“…[82] In contrast to zwitterions featuring BPh 4 À or Bcat 2 À that rely on h 6 -arene interactions to bind a formally cationic PGM fragment, the three MÀP linkages featured in k 3 -[RBP 3 ]ML n complexes serve to anchor the borate ligand to the metal, thereby affording more robust zwitterionic structures. The crystallographically determined M···B distances in ruthenium, [83,84] rhodium and iridium, [82,83,[85][86][87] and platinum [88] [82] Subsequent studies confirmed the ability of 20 to participate in analogous double geminal SiÀH and GeÀ H bond activation processes with other secondary silanes (for example with R = Me, Et, or Ph), primary silanes (R = Mes or 2,4,6-triisopropylphenyl), and Mes 2 GeH 2 . [86] However, the course of such E À H bond activation chemistry was found to be sensitive to the nature of the substituents at phosphorus within the [RBP 3 ] ligand; analogous reactions of the di(isopropyl)phosphino complex 22 with Et 2 SiH 2 or Ph 2 SiH 2 each afforded the corresponding silyl-capped trihydrido species 23 with loss of 1,3-cyclooctadiene (Scheme 11).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…[82] In contrast to zwitterions featuring BPh 4 À or Bcat 2 À that rely on h 6 -arene interactions to bind a formally cationic PGM fragment, the three MÀP linkages featured in k 3 -[RBP 3 ]ML n complexes serve to anchor the borate ligand to the metal, thereby affording more robust zwitterionic structures. The crystallographically determined M···B distances in ruthenium, [83,84] rhodium and iridium, [82,83,[85][86][87] and platinum [88] [82] Subsequent studies confirmed the ability of 20 to participate in analogous double geminal SiÀH and GeÀ H bond activation processes with other secondary silanes (for example with R = Me, Et, or Ph), primary silanes (R = Mes or 2,4,6-triisopropylphenyl), and Mes 2 GeH 2 . [86] However, the course of such E À H bond activation chemistry was found to be sensitive to the nature of the substituents at phosphorus within the [RBP 3 ] ligand; analogous reactions of the di(isopropyl)phosphino complex 22 with Et 2 SiH 2 or Ph 2 SiH 2 each afforded the corresponding silyl-capped trihydrido species 23 with loss of 1,3-cyclooctadiene (Scheme 11).…”
mentioning
confidence: 83%
“…[87] The utility of [RBP 3 ]-ligated PGM species in catalysis remained undocumented until the use of zwitterions 24 and 25 as pre-catalysts for the selective hydrogenation of a,bunsaturated substrates was reported in 2009. [83] Both 24 and 25 proved to be particularly efficient catalysts for the selective hydrogenation of cinnamaldehyde (26) to the corresponding allyl alcohol 27, with the ruthenium zwitterion 25 being one of the most efficient catalysts known for this transformation (Scheme 12).…”
mentioning
confidence: 99%
“…It was hoped that by implementing 2 as the ligand, the high electron-donating ability of the di-isopropylphosphino groups would facilitate the loss of anthracene with concomitant nitride transfer to generate the desired Ni N subunit, but this did not occur. More recent work has focused on second row transition metals such as rhodium [31,32] and ruthenium [32,33]. Rhodium derivatives have displayed a wide range of chemistry, with many reported complexes (64-76, Scheme 12) [32,34,35].…”
Section: Boron (R'b(ch 2 Pr 2 ) 3 -)mentioning
confidence: 99%
“…More recent work has focused on second row transition metals such as rhodium [31,32] and ruthenium [32,33]. Rhodium derivatives have displayed a wide range of chemistry, with many reported complexes (64-76, Scheme 12) [32,34,35]. As these complexes have been studied as hydrogenation and hydrogen transfer catalysts, several complexes feature Rh-H fragments (67, 68, 72 and 74).…”
Section: Boron (R'b(ch 2 Pr 2 ) 3 -)mentioning
confidence: 99%
See 1 more Smart Citation